The Grammatical Errors in Debate Arguments Made by Students of Global English Language Center - Nikmawati, Adina; Syahri, Indawan; Susanti, Rini (JOURNAL OF ADVANCES IN LINGUISTICS, 2018)
The thesis entitled Grammatical Errors in Debate Arguments Made by the Students of Global English Language Center. The objectives of this study were (1) to find out the kinds of errors made by the students of Global English Language Center in their debate arguments and (2) to find out the causes of errors made by the students of Global English Language Center in their debate arguments. The writer used descriptive-qualitative method of research. The population of this study was all the students of Global English Language Center. The sample was chosen by using purposive sampling. The samples were 12 students which were grouped into two debate sessions. The data were calculated and analyzed based on surface strategy taxonomy and linguistic category taxonomy to know the errors. Samples' personal reasons and personal judgement were used to know the causes of the errors. The findings showed that there were four types of errors that the students made which are omission, addition, misformation, and misordering. Misformation is the major error made by the students. Nervousness, time limit, native language interference, and the insufficient grammar learning were the causes why the students made errors.